ダイ7ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1966-1967 - 松田, 達郎; マツダ, タツロウ; MATSUDA, Tatsuro (国立極地研究所, 1968)
P(論文) 1. Syowa Station was enlarged on the opportunity of its reopening. Various huts to accomodate the equipments were constructed, including the new power hut which housed two 45KVA diesel electric generators, a pre-heating hut housing a circulation flush toilet and a preheating tank, and radio and transmitter huts. The transmitter hut was installed appart from the main huts to prevent the interference of electric waves. The buildings were connected by a passageway made of corrugated iron pipes. 2. The 7th wintering party led by Dr. A. MUTO consisted of eighteen members. Activities accomplished between February 1966 and January 1967 were as follows : Upper atmospheric physics, meteorology, biology, seismology, cartography, geology, glaciology, oceanography. 3. In the new power hut, two 45KVA diesel electric generators were working alternately and no power stoppage was recorded during the year. However, the maximum power consumption had once amounted to 43kW. The water supply is most important for the life in the Antarctic. In the summer season, water was obtained from a pond near the base by 441HL unimog with a 600l tank. When it became too cold to get water from the pond, snow was the only source of water. During this winter they experimentally used the water tanks which they made from the corrugated iron pipe lined with a canvas sheet, and the tanks were filled up with snow. The capacity of the tanks was 6 tons altogether. In the kitchen, the water supply system was completed and the cold water and hot water (+45℃) were supplied constantly. The circulation flush toilet was established in a pre-heating hut, and the excrement and the water from kitchen and from bath were pumped out to the sea. Sations that communicated with Syowa Station were Choshi (Japan), KDD (Japan), Mawson, Molodezhnaya, Roi Boudouin, SANAE and the icebreaker FUJI. 4. The inland trip by the newly-developed oversnow vehicle (KD 601) was an important subject. However, as one of the KD 20 oversnow vehicles lost under the sea and another KD ...